Influence of TiO2 content on phase evolution, microstructure and properties of fluorcanasite glass-ceramics prepared through sintering procedure for dental restoration applications. Issue 6 (15th April 2018) - Takav, Pouya; Banijamali, Sara; Sedaghat Ahangari Hossein Zadeh, Ali; Mobasherpour, Iman
Abstract: This study aims to highlight the role of TiO2 (titanium dioxide) on concurrent densification-crystallization behavior, microstructure as well as mechanical and chemical properties of fluorcanasite glass-ceramics. According to the obtained results, the addition of TiO2 to the base composition (stoichiometric fluorcanasite) and an increase of its content, decreased crystallinity of the relevant glass-ceramics; but improved their sinterability. Fully densified glass-ceramics were obtained from TiO2 containing compositions after sintering at 900–950 °C. Calcium fluoride and fluorcanasite crystallized in all fabricated glass-ceramics during sintering; while goetzenite crystallized as the dominant crystalline phase in those glass-ceramics contained more than 6 weight ratios of TiO2 . On the basis of microstructural observation, the interlocking status between the precipitated crystals was remarkably diminished by an increase of TiO2 content. Measurement of mechanical properties confirmed the rise of Vickers micro-hardness and simultaneous decrease of flexural strength and fracture toughness by enhancing of TiO2 content in the examined glass-ceramics.